Contrasting Global Patterns of Spatially Periodic Fairy Circles and Regular Insect Nests in Drylands. Issue 11 (8th November 2019) - Getzin, Stephan; Yizhaq, Hezi; Cramer, Michael D.; Tschinkel, Walter R.
Abstract: Numerical analysis of spatial pattern is widely used in ecology to describe the characteristics of floral and faunal distributions. These methods allow attribution of pattern to causal mechanisms by uncovering the specific signatures of patterns and causal agents. For example, grassland‐gap patterns called fairy circles (FCs) in Namibia and Australia are characterized by highly regular and homogenous distributions across landscapes that show spatially periodic ordering. These FCs have been suggested to be caused by both social insects and competitive plant interactions. We compared eight Namibian and Australian FC patterns and also modeled FCs to 16 patterns of social insect nests in Africa, Australia, and America that include the most regular termite mound patterns known. For pattern‐process inference, we used spatial statistics based on both nearest‐neighbor analysis and neighborhood‐density functions. None of the analyzed insect‐nest distributions attain the spatially periodic ordering that is typical of FCs. The inherently more variable patterns of termite and ant nests are commonly attributable to well documented aspects of the faunal life‐history. Our quantitative evidence from drylands shows that the more variable insect‐nest distributions in water‐limited environments cannot explain the characteristic spatial signature of FCs. The analysis demonstrates the interpretation of scale‐dependent neighborhood‐density functions and that it is the identification of unique spatial signatures in regular patterns that need to be linked to process. While our results cannot verify a specific hypothesis, they support the hypothesis that FCs in these drylands are more likely an emergent vegetation pattern caused by strong plant competition for water. Key Points: Regular spatial patterns are common in ecology, but highly ordered patterns with spatial periodicity like fairy circles (FCs) are rare Based on 25 data sets worldwide, we show that typical termite and ant nest patterns in drylands are systematically less ordered than the FCs We identify termites in drylands as an unlikely cause for periodic FC patterns and discuss plant self‐organization as an alternative cause